Solid state synthesis of europium and praseodymium doped silicate oxyapatites phosphor - Nyang, Tze Wei (2010)
Silicate oxyapatites with (1) varying concentration of Europium (Eu) and Praseodymium (Pr) (Formula: Sr2Y8 – x Kx (SiO4)6O2, where K= Eu, Pr) and (2) varying divalent cation (Formula: A2Y7.9 K0.1 (SiO4)6O2, where A = Strontium (Sr), Calcium (Ca), Magnesium (Mg) and K= Eu, Pr) were prepared using solid state synthesis method. Stoichiometric amounts of powder materials were being mixed and dissolved in ethanol before being ball-milled for 12 hours. The powder samples were then sintered in furnace at 1400oC for 6 hours.